Analisis Literatur Inovasi Pembelajaran Media Digital dalam Pengajaran Akidah Akhlak - Nur Asyifa Ananda; Santiani Santiani (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study analyzes digital media learning innovations in teaching aqidah and akhlak in the digital era. With the advancement of information technology, digital media has become an important tool to increase student engagement and understanding of aqidah values. The use of interactive media, such as animated films and multimedia applications, has proven effective in enriching the learning experience and increasing student motivation. Although there are challenges, such as lack of training for teachers and gaps in access to technology, a comprehensive strategy can help overcome these obstacles. The integration of digital literacy in aqidah education has also been identified as an important aspect to prepare students to face modern challenges. The results of the study indicate that the use of digital media not only supports the delivery of material but also contributes to the formation of student character. It is hoped that this study can be a reference for the development of more innovative and effective teaching methods in the context of aqidah and akhlak education.